Maintaining the flow Water Environment '98, 26 March 1998, London, UK. (Thomas Telford, 1998)
This publication presents the proceedings of a biennial conference by the ICE/CIWEM, and applies to all aspects of the water cycle from water resources to water supply, including the treatment and re-use of wastewater. The book is of benefit to those concerned with the design, management and maintenance of water and wetland regions.